Young People at Destiny’s Crossroads - Professional vocation - Nina Stănescu (Technium Social Sciences Journal, 2021)
Adolescence, known as the most colorful period of personality development, deals with a variety of issues, one being the choice of a future profession. The formula for the right profession choice is: I want – I can – I must, where ”I want” integrates personal interests, motivations and needs; ”I can” expresses individual inclinations, skills and abilities compared to those around them; ”I must” implies the current and prospective needs and requirements of the workforce and the emergence of new professions. The changes proposed in the last decades within the socio-economic life on the whole, especially in the sphere of production and education, have determined the emergence of new characteristics and tendencies in the theory and practice of school and professional orientation. These tendencies and characteristics, outlined in accordance with the current dimensions of the technical-scientific revolution, are common to most national orientation systems and manifest both in terms of concepts and in the field of practice itself [1] in most contemporary countries, orientation has exceeded the stage of a psychodiagnostic action and professional guidance, becoming an educational action which aims to achieve a dynamic balance between the possibilities of the individual, the requirements of the professions and the social needs of the workforce. The assertion of this tendency in the practice of school and professional orientation is based on the expansion of the psycho-pedagogical conception about orientation in more and more countries of the contemporary world, where it is argued that school and professional orientation is a long educational process, which aims to develop the personality of young people in view of the school and professional options and their future social and professional integration.